(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Comparative Politics is a study in the direction of expanding horizon of Political Science. It is an inquiry into political fact through modern methods and techniques. It’s not a policy report, but governments with decision-making at all levels. Formal study of the so-called foreign governing studies, in which disciplined, historical or juridical treatment was given to the governmental structures and formal organizations of state constitutions, emphasized primarily written documents such as the constitution and legal principles on the assignment of political power. As discipline, comparative politics is important, as many studies are now underway with new methods, new concepts and new research instruments. Maybe because of the broad sense of deception and frustration with the conventional descriptive approach to the subject, the main reason for intellectual growth. The word comparative politics refers historically to a subject matter, a specialization area of political academic studies ( i.e., political science), and a method of study of politics. The domestic politics of countries or peoples is the subject of Comparative politics. Comparative politics is not a case-by-center study of political systems but by generalizing and comparing them.